2008
DOI: 10.1039/b717541h
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picosecond fluorescence evolution of amino-cyano-stilbenes in methanol: polar solvation obeys continuum theory without evidence of twisting

Abstract: The spectral evolution of fluorescence from 4-(dimethylamino)-4'-cyanostilbene (DCS) in methanol, and of two derivatives bearing either the anilino (ACS) or the julolidino (JCS) moiety, was measured by optical Kerr-gating with a time resolution of 0.35 ps. A special thin Glan polariser in the Kerr shutter allows high contrast without unnecessarily increasing the group delay dispersion. The emission band may thus be gated and observed even with highly fluorescent samples. The spectral dynamics consists of a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…[37] Even though the solvatochromic measurements are performed over a limited range of the solvent polarity scale, the dipole moment change (µ ge ) can be estimated to 15 ± 1 D and 19 ± 2 D for chromophores 3 and 5 respectively. Such values are of the same magnitude as those obtained for 'push-pull' trans-stilbenes such as 4-cyano-4'-dimethylaminostilbene [38] (~ 15 D) or 4-methoxy-4'-nitrostilbenes [33], [39] (~ 23 D) and therefore illustrate the significant CT character of the emitting states.…”
Section: Excited-states Propertiessupporting
confidence: 64%
“…[37] Even though the solvatochromic measurements are performed over a limited range of the solvent polarity scale, the dipole moment change (µ ge ) can be estimated to 15 ± 1 D and 19 ± 2 D for chromophores 3 and 5 respectively. Such values are of the same magnitude as those obtained for 'push-pull' trans-stilbenes such as 4-cyano-4'-dimethylaminostilbene [38] (~ 15 D) or 4-methoxy-4'-nitrostilbenes [33], [39] (~ 23 D) and therefore illustrate the significant CT character of the emitting states.…”
Section: Excited-states Propertiessupporting
confidence: 64%
“…In initial work, a difficulty was presented by the limited extinction ratio of a polarizing wire grid, 10,11 but this drawback has since been removed by the use of a thin Glan polarizer. 12,13 Only the achievable width ∆t of the instrumental response function is larger compared to other methods, when the optimal Kerr medium (benzene) is used.…”
Section: Introductionmentioning
confidence: 99%
“…Here we test that principle for broadband fluorescence upconversion spectroscopy (FLUPS). [4][5][6][7] Fluorescence gating has been performed with a Kerr shutter, [8][9][10][11][12][13][14][15] by non-collinear optical parametric amplification [16][17][18][19][20] or by diffraction from a transient grating, 21 in addition to broadband upconversion schemes. [4][5][6][7][22][23][24][25] Here we consider only reports where spontaneous emission from molecular or similar sources is gated, dispersed, and registered simultaneously at all relevant wavelengths with a view to obtain true molecular spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved fluorescence studies of DCS type systems indicate presence of at least two species in their excited state. The dual fluorescence in such systems has been attributed to the twist over the single bond attached to aryl and donor Ar-N group (single bond attached to NH 2 ) [40,42]. Our group has found solvent dependent dual fluorescence in cyano-and methoxysubstituted stilbenes [39,40] (Fig.…”
Section: Excited State Charge Transfer Processes In Diphenylpolyenesmentioning
confidence: 92%
“…It has been shown that N,N-dimethylamino-p-cyano stilbene (DCS) and its derivatives exhibits dual fluorescence due to the existence of LE and CT excited states [33][34][35][36][37][38][39][40][41][42]. Such systems show large solvatochromic, red-shifted fluorescence with high fluorescence quantum yield (Φ f ).…”
Section: Excited State Charge Transfer Processes In Diphenylpolyenesmentioning
confidence: 99%